Studies on the Degradation of Fibrinogen by Proteolytic Enzymes from the Larvae of Lanomia achelous (Cramer) - Arocha-Piñango, C L; Perales, J; Carvajal, Z (Thrombosis and Haemostasis, 1981)
Fibrinogen degradation products formed by the action of purified haemolymph and saliva of a Satumidae caterpillar of the Lonomia genus were studies by immunoelectrophoresis and polyacrylamide/SDS gel electrophoresis.The pattern of degradation differ form the one described for plasmin, trypsin, brinase and ochrase. The most striking difference being the rapid loss of the a chain in spite of the presence of the protease inhibitor aprotinin, and/or denaturalizing agents such as 8 M Urea and 2% SDS.
Keywords: Caterpillar haemolymph and saliva; Fibrinogen degradation